IMPLEMENTATION OF MULTI-CONTRACT IB HIJRAH RENCAN SAVINGS PRODUCT AT BANK MUAMALAT - Triyatno, Ghazy; Novianti, Irodathul; Munir, Misbahul; Khasanah, Umrotul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The purpose of this research is to explain the contract process applied to the iB Hijrah Rencana savings product offered by Bank Muamalat. Descriptive qualitative analysis is used as the research method; in other words, the research subject is systematically described concerning the core issue. This research aims to understand how multiple contracts are implemented at Bank Muamalat and how the profit-sharing ratio for the Rencana savings product is applied at Bank Muamalat from the perspective of Islamic economics. The results show that there are two contracts in the implementation of the iB Hijrah Rencana savings: mudharabah mutlaqoh and tabarru’/sharia insurance. The implementation of the profit-sharing ratio at Bank Muamalat uses a profit-sharing system based on the net results from managing the funds, which is from the perspective of Islamic economics. This is because the transaction basis adheres to the DSN-MUI fatwa No.02/DSN-MUI/IV/2000. This method is expected to help realize the community's dreams in executing their planned activities. With this product, there is no longer any concern that funds intended for worship purposes will be mixed with riba.